Understanding the Role of Artificial Intelligence in Personalized Engagement Marketing. (August 2019) - Kumar, V.; Rajan, Bharath; Venkatesan, Rajkumar; Lecinski, Jim
This article explores the role of artificial intelligence (AI) in aiding personalized engagement marketing—an approach to create, communicate, and deliver personalized offerings to customers. It proposes that consumers are ready for a new journey in which AI is a tool for endless options and information that are narrowed and curated in a personalized way. It also provides predictions for managers regarding the AI-driven environment on branding and customer management practices in both developed and developing countries.